2000
DOI: 10.1111/j.1095-8649.2000.tb02177.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetc divergence and phylogeny of the Salmoninae based on allozyme data

Abstract: The data on 31-37 allozyme loci in 21 species of nine salmonid genera are used for phylogenetic analysis by seven distance methods and several variants of cladistic analysis. Monophyletic origin for all genera and three sub-families of the Salmonidae is corroborated. The closest phylogenetic relationships are characteristic of Parasalmo and Oncorhynchus (bootstrap support is 88-99%), Brachymystax and Hucho (68-97%), and the clade (Brachymystax+ Hucho)+Salmo (up to 85%). The patterns of phylogenetic relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…margaritifera and M . dahurica may be evidence of close evolutionary relations of their host-fishes, and correspond well to the findings of Osinov and Lebedev 71 and Artamonova et al . 70 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…margaritifera and M . dahurica may be evidence of close evolutionary relations of their host-fishes, and correspond well to the findings of Osinov and Lebedev 71 and Artamonova et al . 70 .…”
Section: Discussionsupporting
confidence: 91%
“…Numerous studies are dedicated to investigation of molecular phylogeny of salmonids, in particular evolutionary interactions between the genera Brachymystax , Hucho , and Salmo 70 . Osinov and Lebedev 71 , using a large dataset of protein-coding genes, revealed that Brachymystax , Hucho and Salmo belong to the same clade. An analysis of amino acid partial sequences of the COI returned the same result 70 .…”
Section: Discussionmentioning
confidence: 99%
“…Originally, Salmoninae phylogenetic rebuilding has permitted Parahucho perryi to also be found in a variety of positions within the group, including sibling Salvelinus [ 218 , 241 ], Salmo [ 158 , 223 ], and the rest of Salmoninae [ 232 , 242 , 243 ]. Based on these data, it has been suggested that Coregoninae is a sister group to the rest of the Salmonidae [ 217 , 244 ]. Recent genetic investigations of the subfamily Thymallinae utilizing genome-wide mitochondrial genome sequencing confirmed the relatedness of the three subfamilies Coregoninae , Thymallinae , and Salmoninae but left confusion regarding the evolutionary connections between the long-recognized subfamilies [ 244 , 245 ].…”
Section: Phylogenetic Characteristics Of Salmonmentioning
confidence: 99%
“…Based on these data, it has been suggested that Coregoninae is a sister group to the rest of the Salmonidae [ 217 , 244 ]. Recent genetic investigations of the subfamily Thymallinae utilizing genome-wide mitochondrial genome sequencing confirmed the relatedness of the three subfamilies Coregoninae , Thymallinae , and Salmoninae but left confusion regarding the evolutionary connections between the long-recognized subfamilies [ 244 , 245 ]. Other monotypic genera, such as Salvethymus in the Salmoninae and Stenodus in the Coregoninae , have distinct morphologies and karyotypes that set them apart from other genera in their respective subfamilies, although certain molecular data show that they possess not justify genus classification [ 185 , 218 , 236 , 241 , 243 , 246 , 247 , 248 ].…”
Section: Phylogenetic Characteristics Of Salmonmentioning
confidence: 99%
“…Salmonidae contains many of the most economically and ecologically important temperate freshwater fishes, which, due to their common tetraploid ancestry (Allendorf and Thorgaard 1984), attract considerable attention in evolutionary research. The subfamily Thymallinae (graylings), considered a distinct family by Skurikhina et al (1985) and Osinov and Lebedev (2000), is less well known, although the recognized species diversity has increased considerably over the past 15 years (Antonov 2004;Knizhin et al 2006aKnizhin et al , 2007Knizhin and Weiss 2009). Additionally, increased conservation concerns over European grayling Thymallus thymallus (Dawnay et al 2011;Weiss et al 2013;Mueller et al 2018), as well as its recent whole-genome sequencing (Varadharajan et al 2018;Sävilammi et al 2019), have opened the doors to more focused evolutionary and conservation management research (Papakostas et al 2014;Mäkinen et al 2016;Huml et al 2018).…”
Section: Introductionmentioning
confidence: 99%